Determinación de Helicobacter Pylori en adultos mayores y su relación con la diabetes mellitus, en pacientes que acuden al Dispensario Médico Reina del Cisne. - Guachón Patiño, Inés Rocio (2013)
Infection by Helicobacter pylori, is a serious public health problem, being also important its relationship with certain medical conditions outside of the scope of the digestive pathology, such as Diabetes Mellitus, present especially in the elderly, these patients refer the presence of digestive symptoms, due to autonomic neuropathy, which affects the nervous system, manifesting itself in digestive motility disorders, thus also direct effect on blood sugar levels and at the same time the bacterial proliferation of Helicobacter pylori as a result of imbalances in your immune system. In view of the present reality is a study descriptive and transversal, entitled cutting "Determination of Helicobacter pylori in older adults and its relation with diabetes mellitus in patients attending the medical dispensary 'Swan Queen', the study was applied to 100 adults of both sexes, who determined glucose in blood, by the colorimetric enzymatic method"to differentiate between 50 diabetic patients and 50 non-diabetics. Also detected the presence of Helicobacter pylori in stool using the Immunochromatographic method, determining the 37% of positive patients, in which the age of greatest risk is between 60-80 years and a greater percentage of female sex. Likewise detected the relationship between diabetic and non-diabetic patients in study, with infection with Helicobacter pylori, for which applied the table from 2 x 2 whose results were determined, that if there is a relationship between these two variables. He was the dissemination of the results to people who are part of the study, which was conducted with older adults who come to the clinic "Queen of the Swan". Located in the barrio San Pedro, Sucre, Loja cantón parish. The findings of the present investigation, consistent with the objectives set. Keywords: Helicobacter pylori, Diabetes Mellitus, older adult.